The Utilization of Accounting Information for Business Forecasting among Small and Medium Enterprises (SMEs) in Nong Khaem District, Bangkok - Davis, Murray; Changkomchome, Thanawan; Thaweedech, Thikamporn; Tanskul, Kawissara (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This study is a quantitative research project aimed at investigating the effective utilization of accounting information for business forecasting within small and medium enterprises (SMEs). Data were collected via questionnaires from a sample group of 400 participants, consisting of executives, supervisors, and accountants from SMEs registered in Nong Khaem District, Bangkok. The statistical analysis employed Stepwise Multiple Regression Analysis to test the hypotheses.          The findings indicate that the utilization and analysis of accounting information-specifically data from income statements, statements of financial position, and statements of cash flows, along with trend analysis and financial ratio analysis-significantly contribute to business forecasting for SMEs in Nong Khaem. The adjusted coefficient of determination (Adjusted R Square), used to compare models with varying numbers of predictors, was 0.802. This suggests that these variables can collectively explain 80.2% of the positive influence on effective business forecasting. The specific accounting components utilized for forecasting, in order of statistical significance (at the 0.05 level), include: trend analysis (b=.528), financial ratio analysis (b=.261), income statement data (b=.180), balance sheet data (b=.099), and statement of cash flows (b=.088).